2018
DOI: 10.1590/1414-431x20187558
|View full text |Cite
|
Sign up to set email alerts
|

Cat ownership is associated with increased asthma prevalence and dog ownership with decreased spirometry values

Abstract: The association between pet ownership and the development of allergic and respiratory diseases has been the aim of several studies, however, the effects of exposure in adults remain uncertain. The aims of the present study were to investigate the prevalence of asthma and lung function status among dog and cat owners. This cross-sectional study was performed at two universities with students and workers who were allocated into 3 groups according to pet ownership in the previous year: cat owners, dog owners, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
8
0
2
Order By: Relevance
“…In those with a formal diagnosis of atopic conditions, we found that self-reported symptoms of allergic rhinitis worsened with pet acquisition while those of allergic rhinitis and eczema subsequently improved when pet ownership ceased. Pets may serve as allergen sources [22][23][24]56 , with a study showing that fur-bearing animals exacerbated symptoms of pre-existing perennial allergic rhinitis 57 . Conversely, other studies have described that pet ownership may be associated with a reduced risk of developing atopic diseases 58 as a result of allergen desensitisation [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those with a formal diagnosis of atopic conditions, we found that self-reported symptoms of allergic rhinitis worsened with pet acquisition while those of allergic rhinitis and eczema subsequently improved when pet ownership ceased. Pets may serve as allergen sources [22][23][24]56 , with a study showing that fur-bearing animals exacerbated symptoms of pre-existing perennial allergic rhinitis 57 . Conversely, other studies have described that pet ownership may be associated with a reduced risk of developing atopic diseases 58 as a result of allergen desensitisation [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Another dimension of interest is the effect of pet ownership on atopic conditions (asthma, allergic rhinitis and eczema). Whilst there are studies suggesting that pet ownership or animal exposure protects against the development of atopic conditions 15 18 via allergen desensitisation, other studies claim that animals otherwise serve as sources of allergens 19 that may result in higher rates of diagnosis or worsening of atopic conditions 20 24 .…”
Section: Introductionmentioning
confidence: 99%
“…This concept has recently been challenged, and indeed such association has been demonstrated. [40] However, such notion should be counterbalanced with studies which propose a protective effect of exposure to cats and dogs as pets in earlier childhood, a concept not far removed from the hygiene hypothesis with regards to infection. [41]…”
Section: Discussionmentioning
confidence: 99%
“…Um trabalho de revisão aprofundado, realizado em 2015, mostrou que até aquele ano o papel da exposição humana a alérgenos de animais domésticos ainda era contraditório e exigia novas abordagens 24 . Mais recentemente, em 2018, foi demonstrado em um estudo chinês que a presença de animais está relacionada ao desenvolvimento de alergias em vias aéreas 25 , em um trabalho brasileiro que a convivência com animais domésticos pode aumentar a prevalência de asma e diminuir os valores de espirometria 12 , e em um trabalho polonês que a convivência com animais domésticos está relacionada ao aumento da frequência de sintomas alérgicos, especialmente da asma 13 .…”
Section: Discussionunclassified
“…A possível relação entre animais domésticos e o desenvolvimento de alergias tem sido discutida na literatura, porém, geralmente focada no desenvolvimento de alergias respiratórias. Recentemente foi descrito que a convivência com gatos e cães pode influir no estado alérgico do dono, sendo a convivência com gatos relacionada a um aumento da prevalência de asma e com cães a uma diminuição dos valores de espirometria 12 . Além disso, já foi demonstrado que a convivência com animais domésticos (cães e gatos) no ambiente urbano está relacionada ao aumento da frequência de sintomas alérgicos, especialmente da asma 13 .…”
Section: Introductionunclassified